Comparison and Synthesis of Sea‐Level and Deep‐Sea Temperature Variations Over the Past 40 Million Years. (18th November 2022) - Rohling, Eelco J.; Foster, Gavin L.; Gernon, Thomas M.; Grant, Katharine M.; Heslop, David; Hibbert, Fiona D.; Roberts, Andrew P.; Yu, Jimin
Abstract: Global ice volume (sea level) and deep‐sea temperature are key measures of Earth's climatic state. We synthesize evidence for multi‐centennial to millennial ice‐volume and deep‐sea temperature variations over the past 40 million years, which encompass the early glaciation of Antarctica at ∼34 million years ago (Ma), the end of the Middle Miocene Climate Optimum, and the descent into bipolar glaciation from ∼3.4 Ma. We compare different sea‐level and deep‐water temperature reconstructions to build a resource for validating long‐term numerical model‐based approaches. We present: (a) a new template synthesis of ice‐volume and deep‐sea temperature variations for the past 5.3 million years; (b) an extended template for the interval between 5.3 and 40 Ma; and (c) a discussion of uncertainties and limitations. We highlight key issues associated with glacial state changes in the geological record from 40 Ma to present that require attention in further research. These include offsets between calibration‐sensitive versus thermodynamically guided deep‐sea paleothermometry proxy measurements; a conundrum related to the magnitudes of sea‐level and deep‐sea temperature change at the Eocene‐Oligocene transition at 34 Ma; a discrepancy in deep‐sea temperature levels during the Middle Miocene; and a hitherto unquantified non‐linear reduction of glacial deep‐sea temperatures through the past 3.4 million years toward a near‐freezing deep‐sea temperature asymptote, while sea level stepped down in a more uniform manner. Uncertainties in proxy‐based reconstructions hinder further distinction of "reality" among reconstructions. It seems more promising to further narrow this using three‐dimensional ice‐sheet models with realistic ice‐climate‐ocean‐topography‐lithosphere coupling, as computational capacities improve. Plain Language Summary: Global ice volume (hence, sea level) and deep‐sea temperature are important measures of Earth's climatic state. To better understand Earth's climate cycles in response to its orbitally driven insolation cycles, we evaluate and synthesize evidence for ice‐volume (sea‐level) and deep‐sea temperature variations at multi‐centennial to millennial resolution throughout the last 40 million years. These last 40 million years encompass the major build‐up of Antarctic glaciation from about 34 million years ago, and development of extensive Northern Hemisphere ice sheets from about 3.4 million years ago. We present a new template synthesis of ice‐volume (sea‐level) and deep‐sea temperature for the past 5.3 million years, with extension through the interval between 5.3 and 40 Ma with wider uncertainties. We also highlight a number of remaining questions about major climate transitions, including the early glaciation history of Antarctica, the end of the so‐called Middle Miocene Climate Optimum from about ∼14.5 Ma, and the descent over the past several million years into conditions with extensive ice‐age maxima in both hemispheres. Key Points: New synthesis of sea level and deep‐sea temperature over 40 million years, at millennial resolution, across seven different methods Discrepancies between Eocene‐Oligocene and Middle Miocene sea‐level reconstructions are highlighted for focussed future research Plio‐Pleistocene glacial deep‐sea temperature asymptoted to a freezing limit by ∼1.25–0.9 Ma; glacial sea‐level minima decreased ∼linearly